The Keystone Drypetes [Drypetes confertiflora (Hook.F.) Pax & Hoffm. (Euphorbiaceae)]: Notes on Ecology, Associations, Limits and Seed Germination - Rakesh, R. R.; Somen, C. K.; Roby, T. J.; Mathew, J. (Indian Forester, 2017)
Drypetes confertiflora is strict endemic and a key stone species in the riparian zonations of evergreen and semi-evergreen forests of Kerala part of Western Ghats, persists on six remaining locations. This study assessed the status analysis and seed germination of this naturally vulnerable plant. The low reproductive success of D. confertiflora leads to the extinction of the species in the nearby future. Successful population reinforcement had been made by nursery techniques to conserve this species. The data presented in this paper would provide useful information for the conservation of this rare and endemic taxa.